A Comparative Analysis of Cantilever and Gravity Retaining Wall Dimensions on The Temuireng-Jetis Road Section In Mojokerto District - Prastya Ramadiasri Putra; Wateno Oetomo; Risma Marleno (Journal of Social Research, 2025)
The construction of retaining walls in Mojokerto Regency is essential due to the region's hilly topography and the increasing risk of slope instability caused by high rainfall and lateral soil pressures. Retaining walls play a crucial role in stabilizing slopes, preventing landslides, and ensuring road infrastructure and mobility are preserved in areas prone to geotechnical challenges. This study focuses on determining the dimensions, costs, and construction timelines of cantilever and gravity retaining walls along the Temuireng-Jetis road section, a strategic route affected by frequent landslides. Using Coulomb's theory and triaxial soil test data, the analysis comprehensively compares the structural stability, safety factors, and economic efficiency of both designs. Results indicate that cantilever retaining walls achieve higher shear stability with a lower construction duration but incur higher costs due to the use of reinforced concrete and steel reinforcements. Conversely, gravity walls are more cost-effective, relying on their own weight for stability, but demand longer construction periods due to their massive size and additional requirements such as drainage systems. These findings contribute to efficient and sustainable infrastructure development, offering practical solutions for areas with varying topographic challenges and soil conditions.